Fibromyalgia Syndrome in Chronic Obstructive Pulmonary Disease - Jassim, Nizar A.; Gorial, Faiq I.; Al-Rawi, Ziad Sh.; Khleif, Ali H. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Fibromyalgia syndrome is a common rheumatological syndrome with multiple systemic manifestations & associated with many diseases. The aim of the study is to assess the possible association between fibromyalgia syndrome (FMS) & chronic obstructive pulmonary disease (COPD), and to correlate this association with patient’s age, age group, sex, marital status, duration of the disease, & its severity. Patients and Methods: Fifty patients with COPD & 50 healthy controls were included in this study. Full history was taken & complete physical examination was done for all patients in both groups. Disease characteristics [age, age group, sex, marital status, duration of the disease, & severity of COPD) were also documented. Pulmonary function tests and chest-X-ray were evaluated for all patients. The American College of Rheumatology (ACR) 1990 Criteria for the classification of FMS were applied to all patients & controls included in this study for diagnosis of FMS. Results: Four (8%) patients with COPD have FMS compared with 3(6%) controls (p=0.695). Also FMS was reported in 3 (16.7%) female patients with COPD compared with 1 (3.1%) male patient with COPD (p=0.04). There was no statistical significant association between FMS and: patient’s age, age group, marital status, duration of the disease, & disease severity (p=0.816, p=0.481, p=0.702, p=0.178, p=0.181) respectively. Conclusions: FMS is more common in COPD patients compared to controls, but no statistical significant association between them. There was a statistical significant association between FMS & patient’s sex only.